England Looks to the Future: The Cultural Forum Model and Doctor Who. - Gregg, Peter B. (Journal of Popular Culture (Wiley-Blackwell), 2004)
This article focuses on The Ark in Space, a four-part television serial created by producer Philip Hinchcliffe script editor Robert Holmes, starring Tom Baker as the Doctor. Borrowing from Newcomb and Hirsch's cultural forum model of television rhetoric. Newcomb and Hirsch argue that a cultural focus as basis for the analysis and criticism of television is the bridge between a concern for television as a communications medium, central to contemporary society, and television as an aesthetic object, the expressive medium that unites and examines a culture. When viewing a television show as a cultural forum, the historical and cultural context plays an essential role. The future as demonstrated by The Ark in Space has room for British culture, a fear probably arising from England's European Union entrance. Instead of American or continental voices, all characters, including the future prime minister of the planet, have an English accent. The narrative allows a viewer to imagine that no matter how difficult the situation in the present, the English way can still survive if it can develop unfettered by outside, un-British, or alien forces. The key differences between The Ark in Space and other shows of the science fiction genre help to make it more successful than the competing discourses. The Ark in Space willingly uses humor to defuse dramatic situations, unlike Space: 1999 or Star Trek. The cultural forum model illuminates The Ark in Space as a text rich in meaning deriving from and responding to the needs of its viewers.